Effects of different water storage procedures on the dissolved Fe concentration and isotopic composition of chemically contrasted waters from the Amazon River Basin†. (1st October 2015) - Mulholland, Daniel S.; Poitrasson, Franck; Boaventura, Geraldo R.
<x xml:space="preserve">Abstract</x> Rationale Although recent studies have investigated the Fe isotopic composition of dissolved, colloidal and particulate phases from continental and oceanic natural waters, few efforts have been made to evaluate whether water sample storage and the separation of different pore‐size fractions through filtration can cause any change to the Fe isotopic compositions. The present study investigates the possible biases introduced by different water storage conditions on the dissolved Fe concentration and isotopic composition of chemically different waters. Methods Water samples were collected from an organic‐rich river and from mineral particulate‐rich rivers. Filtered and unfiltered water samples were stored either at room temperature or frozen at –18°C in order to assess possible biases due to (i) different water storage temperature, and (ii) storage of bulk (unfiltered) vs filtered water. Iron isotope measurements were performed by Multicollector Inductively Coupled Plasma Mass Spectrometry with a Thermo Electron Neptune instrument, after Fe purification using anion‐exchange resins. Results Our data reveal that bulk water storage at room temperature without filtration produces minor changes in the dissolved Fe isotopic composition of mineral particulate‐rich waters, but significant isotopic composition changes in organic‐rich waters. In both cases, however, the impact of the different procedures on the Fe concentrations was strong. On the other hand, the bulk water stored frozen without filtration produced more limited changes in the dissolved Fe concentrations, and also on isotopic compositions, relative to the samples filtered in the field. The largest effect was again observed for the organic‐rich waters. Conclusions These findings suggest that a time lag between water collection and filtration may cause isotopic exchanges between the dissolved and particulate Fe fractions. When it is not possible to filter the samples in the field immediately after collection, the less detrimental approach is to freeze the bulk water sample until filtration, to reduce isotopic artifacts. Copyright © 2015 John Wiley & Sons, Ltd.